Capacidad antioxidante del néctar de prunus pérsica (durazno) y aloe vera (sábila) in vitrio con el 2,2 difenil – 1 – picrilhidrazilo (dpph*) - Reynoso Leyva, Elva Milagros (2014)
The antioxidant capacity of Prunus persica nectar (peach) and Aloe vera (aloe) In vitrio with DPPH * was determined. The sample consisted of peach nectar with aloe to 25% in dilute system (10 / 100ml) By filling WILLIAMS BRAND method, which is mixed with DPPH * 0.1 Mm, these absorbance reading was performed 517nm. It is concluded that the antioxidant capacity of Prunus persica nectar "peach" 25% uptake generates free radicals, thus demonstrating its antioxidant capacity. Also, the rate of capture of DPPH increases as the concentrations and the time increases